2019
DOI: 10.1016/j.scitotenv.2019.02.196
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal from coke making wastewater through a pre-denitrification activated sludge process

Abstract: Under the Industrial Emissions Directive (IED), coke production wastewater must be treated to produce an effluent characterised by a total nitrogen (TN) <50 mg/L. An anoxic-aerobic activated sludge pilot-plant (1 m 3) fed with coke production wastewater was used to investigate the optimal operational requirements to achieve such an effluent. The loading rates applied to the pilot-plant varied between 0.198-0.418 kg COD/m 3 .day and 0.029-0.081 kg TN/m 3 .day, respectively. The ammonia (NH 4 +-N) removals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…The wastewater exhibited a pH of 7.8±0.3. Concentrations of pollutants therefore fell within the typical range for coke wastewater previously reported for this site as well as those reported in the wider literature (Marañón et al, 2008;Raper et al, 2019;Staib and Lant, 2007;Vázquez et al, 2006).…”
Section: Wastewater and Activated Sludge Biomasssupporting
confidence: 87%
See 3 more Smart Citations
“…The wastewater exhibited a pH of 7.8±0.3. Concentrations of pollutants therefore fell within the typical range for coke wastewater previously reported for this site as well as those reported in the wider literature (Marañón et al, 2008;Raper et al, 2019;Staib and Lant, 2007;Vázquez et al, 2006).…”
Section: Wastewater and Activated Sludge Biomasssupporting
confidence: 87%
“…In contrast, however, previous work on the current activated sludge biomass revealed that the biomass was capable of completely removing SCNin both aerobic conditions and anoxic conditions (Raper et al, 2019(Raper et al, , 2017. This SCNdegradation in the anoxic cell of a pilot-scale anoxic-aerobic ASP was possible with biomass taken from an aerobic process without any acclimatisation period.…”
Section: Thiocyanate Degradation In the Mixed Culturecontrasting
confidence: 56%
See 2 more Smart Citations
“…Compared to the Anammox process, the bio-electro-chemical ammonia oxidation did not produce by-product nitrate, associated with electroactive autotrophs. Raper et al (2019) operated an anoxic-aerobic activated sludge pilot plant to evaluate the optimal C/N ratio treating coking wastewater. The results showed that the influent C/N ratio maintained exceed 5.7, could achieved the satisfied ammonia (NH 4 + -N) removals (96%) and the effluent TN less than 50 mg/L, together with the carbon resources during denitrification such as SCN − and phenol remained a stable removal at 100% and 96%, respectively.…”
Section: Nitrogen Removalmentioning
confidence: 99%